Omega Dynamics Manufacturing Inc. A production and operations management study - Empamano, Cherry; Gavino, Marie Abigail E.; Pon-an, Elsie P. (Diliman, Quezon City College of Engineering, 1999)
This paper delved into how Omega Dynamics manufacturing Inc., an umbrella manufacturer manages their production systems. The systems studied by the group includes the company's production planning, operations scheduling, materials management, and purchasing functions. The group conducted an on-sight study of the process involved in making umbrella and pertinent personnel were interviewed. The processes were documented. Then historical data were gathered and analyzed. Using the streamline diagnostic chart, problem areas were identified. Of the numerous problems confronting the company, the group focused on materials management, capacity planning, in balancing the job assignments in production and the evaluation of wage plans. One of the main problems in the company is its frequent lack of raw materials when they are needed. The group found ways on minimizing shortages to prevent delays in production and help the company meet its production schedule by analyzing the inventory management function. Due to time constraints, the group concentrated only in calculating the optimum order quantity for the frame types using the company's current system of a fixed time period inventory system. From the three fixed-time inventory models discussed, the group recommends the use of Model 3 in determining future inventory levels for the different types of frames. Inventory Model 3 calculates 2 different order quantities, depending on the time of the year when the order for the frames is expected to arrive. This inventory model minimizes stockouts especially for product lines with highest demand while giving the lowest inventory holding cost for months of low demand. To be able to effectively use the fixed-time inventory model in calculating order quantities in the future, thew company must use forecasting technique to determine the demand trends among product lines. The company must thus revise their data gathering system. Purchase Order data must segregate demand for different product lines, for easier access to these data, which would aid the company in analyzing the demand trends among product lines. The group also recommends the use of perpetual system in managing all their raw materials inventory. This would provide the Marketing Dept. with up-to-date information regarding the raw materials availability. The group conducted a time study in order to establish the standard times for each operation. The time study aided the group in estimating the plant's capacity in manufacturing umbrellas. It is also a tool in planning the labor requirements to be able to achieve a certain targeted production output requiring overtime as little as possible. The group came up with different job loading assignment alternatives depending on specified production volume per month with the objective of minimizing labor cost. Work sharing schemes were formulated to decrease idle time and to distribute the job evenly. The stitching operation was found out to be the bottleneck operation in the production department. The balance of the job loading assignments is highly dependent on the stitching operation. In order for the company to maintain its schedules, the stitching operation must always have something to work on. The group recommends that production quotas be set for the stitching operation, using the time standard that the group calculated. The group recommends that the workers would be hired on a per hour basis for operations such as cutting, sewing, heading, strapping, quality control, capping and inserting handles because it is cheaper compared to a per piece rate. This also helps in providing a more balanced job loading system. Only on two operations, tipping and stitching should the company pay on a piece-rate basis since the piece-rate wages for these operations minimizes the labor cost. Finally the group recommends that the company should give more effort in marketing their products. The company has too much underutilized capacity. Better marketing strategies is one way of solving their problems on high product cost since an increase in sales will allocate overhead to more products leading to a decrease in per unit cost.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Omega Dynamics Manufacturing Incorporation; Umbrella industry; Production engineering